SADC: Report on Promotion of National and Regional Fisheries and Aquaculture Tradable/nutritious Aquatic Food Products Focusing on SMEs, linkages with Eco-tourism, and Market Connectivity to the AfCFTA - Muzungaire, Lizzy; Siamudaala, Victor; Chileya, Agness; Kakwasha, Keagan; Kanyembo, Henry (Independent / Not associated, 2025)
This report provides valuable insights and recommendations for policymakers, practitioners, and other stakeholders seeking to support the development of small and medium-sized enterprises (SMEs) in the aquatic food sector in Southern Africa. The report highlights the importance of targeted capacity-building programs in addressing the specific needs of SMEs to enhance their capacity to deliver nutrient dense aquatic foods to address household food and nutritional insecurity and in turn promote sustainable development in the region.